1999
DOI: 10.1111/j.1469-7793.1999.351ae.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that multiple P2X purinoceptors are functionally expressed in rat supraoptic neurones

Abstract: The supraoptic nucleus (SON) of the hypothalamus contains cell bodies of two different populations of neurosecretory cells, vasopressin and oxytocin neurones. Release of vasopressin and oxytocin in the neurohypophysis is controlled by the specific electrical activity of these neurones, which is regulated by synaptic inputs into the SON mediated by various neurotransmittersÏneuromodulators, such as GABA and glutamate (Decavel & Van den Pol, 1990;Van den Pol et al. 1990;Wuarin & Dudek, 1993). A1 noradrenergic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 50 publications
6
100
2
2
Order By: Relevance
“…Fluorescence was measured as described previously. 26 In brief, fluorescence was measured from BCECF-loaded cells in a culture dish, which had a thin glass coverslip bottom and was positioned on the stage of an inverted microscope (IX-50; Olympus, Tokyo, Japan), using a fluorescence-imaging system equipped with a 12-bit digital CCD camera (Quanticell/900; Applied Imaging, Sunderland, UK). Once cells were selected in the optical field with the aid of the microscope, fluorescence intensities at 540 nm (Ϯ30 nm bandwidth) with excitation at 440 and 490 nm were recorded at an interval of 5 sec.…”
Section: Phi Measurementsmentioning
confidence: 99%
“…Fluorescence was measured as described previously. 26 In brief, fluorescence was measured from BCECF-loaded cells in a culture dish, which had a thin glass coverslip bottom and was positioned on the stage of an inverted microscope (IX-50; Olympus, Tokyo, Japan), using a fluorescence-imaging system equipped with a 12-bit digital CCD camera (Quanticell/900; Applied Imaging, Sunderland, UK). Once cells were selected in the optical field with the aid of the microscope, fluorescence intensities at 540 nm (Ϯ30 nm bandwidth) with excitation at 440 and 490 nm were recorded at an interval of 5 sec.…”
Section: Phi Measurementsmentioning
confidence: 99%
“…Double-labeling fluorescence immunohistochemistry has shown that both vasopressin-and oxytocin-containing neurons in the SON express P2X2, P2X4 and P2X5 receptor proteins (Guo et al, 2009). P2X2R-positive immunoreactivity has been found both on SON somata and nerve fibers (Yao et al, 2003;Vulchanova et al, 1996;Xiang et al, 1998;Shibuya et al, 1999;Loesch and Burnstock, 2001). Our quantitative reverse transcription-polymerase chain reaction (qRT-PCR) analysis showed the expression of mRNAs of all P2XR subunits and several P2YRs in SONcontaining tissue; the expression of mRNAs for ionotropic P2X2R > P2X7R > P2X4R subunits was the most significant ( Fig.2) (Vavra et al, 2011).…”
Section: Expression Of P2x Receptor Subtypes In Hypothalamusmentioning
confidence: 97%
“…P2X2, P2X4 and P2X6, but not P2X5 receptor mRNAs have been identified in the rat supraoptic nucleus (SON), ventromedial nucleus, paraventricular nucleus, arcuate nucleus, suprachiasmatic nucleus, and several other hypothalamic areas using in situ hybridization; the P2X1, P2X3 and P2X7 receptors were not tested in this study (Collo et al, 1996). Another PCR analysis revealed that P2X2, P2X3, P2X4, P2X6, and P2X7 receptor mRNAs are expressed in the rat SON neurons; P2X1 and P2X5 mRNAs were not found (Shibuya et al, 1999). In the preoptic area of the rhesus monkey, the P2X2, P2X4 and P2X7 receptor mRNAs, but not P2X1, P2X3 and P2X5 receptor mRNAs, were identified; subunit P2X6 was not examined (Terasawa et al, 2005).…”
Section: Expression Of P2x Receptor Subtypes In Hypothalamusmentioning
confidence: 98%
See 1 more Smart Citation
“…Extracellular adenosine 5'-triphosphate (ATP) is an important excitatory transmitter both in the peripheral and central nervous system [135]. P2X receptors are a distinct family of ligand-gated membrane ion channels activated by ex- Fig.…”
Section: P2x Receptorsmentioning
confidence: 99%